2008
DOI: 10.1007/s11746-008-1297-8
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Fat Content, Free Fatty Acid and Fatty Acid Profile Including trans Fat in Pakistani Biscuits

Abstract: The fat contents of 12 brands of biscuits were extracted and evaluated for free fatty acids (FFA) and their fatty acid composition (FAC). The oil content and FFA varied from 13.7 to 27.6% and 0.2 to 1.0%, respectively. The FAC was analyzed by gas chromatography-mass spectroscopy with particular emphasis on trans fatty acids (TFA). Total saturated, unsaturated, cis-monounsaturated and polyunsaturated fatty acids were determined in the range of 37.9-46.9, 53.0-62.0, 12.3-43.7 and 0.1-9.2%, respectively. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
2
14
2
Order By: Relevance
“…Furthermore, in order to achieve biscuits with desirable characteristics, manufacturers may utilize single fats or many possible combinations of different kind of fats and oils [22,23]. A comparison of the total TFA value for our biscuits with those of the literature revealed that observed levels were lower than those found by other authors who examined Pakistani (26.7%) [14], Brazilian (20.1%) [24] and Turkish biscuits (16.4%) [13], but significantly higher than reported value of Italian biscuits (1.7%) [15].…”
Section: Resultsmentioning
confidence: 61%
“…Furthermore, in order to achieve biscuits with desirable characteristics, manufacturers may utilize single fats or many possible combinations of different kind of fats and oils [22,23]. A comparison of the total TFA value for our biscuits with those of the literature revealed that observed levels were lower than those found by other authors who examined Pakistani (26.7%) [14], Brazilian (20.1%) [24] and Turkish biscuits (16.4%) [13], but significantly higher than reported value of Italian biscuits (1.7%) [15].…”
Section: Resultsmentioning
confidence: 61%
“…The use of 25% margarine and 30% margarine did not have a significant effect on the protein content because the margarine contains 720 kcal / 100 g, fat 81.6 g / 100 g and retinol 606 ug / 100 g. Meanwhile, the protein content which is 0.6 g / 100 g is categorized as quite small (Persatuan Ahli Gizi Indonesia, 2009) The total fat of this yellow corn biscuit was 18.2 -21.7% which is still within reasonable limits when compared biscuits in the market. The results of the study of 12 kinds of biscuits in Pakistan showed that a fat content varied from 13.7 to 27.6% (Kandhro, 2008). The results of analysis of 46 samples biscuit sold in Indian market showed that the total fat content ranged from 9.5 to 25.0 g / 100 g of biscuits (Kala.…”
Section: Resultsmentioning
confidence: 99%
“…For example, higher TFA contents were reported for Pakistani biscuits and French bakery goods for example cakes, crackers, puff pastry, and cookies 17, 18. For instance, the total C18:1 trans content of Pakistani biscuits ( n = 12) ranged from 9.3 up to 34.9 g/100 g fat 17 and in French bakery goods ( n = 16) from 13.0 up to 61.0% of total fatty acids 18. Interestingly, the trans octadecenoic acid profiles of the German ‘Berliner’ type of doughnuts of the present survey (see Fig.…”
Section: Resultsmentioning
confidence: 99%